Geopolymers as Sustainable Surface Concrete Repair Materials - Huseien, Ghasan Fahim; Abdul Rahman Mohd Sam; Mahmood Md. Tahir (Emerging Materials and Technologies, 2023)
The progressive deterioration of concrete surface structures is a major concern in construction engineering that requires precise repairing. While a number of repair materials have been developed, geopolymer mortars have been identified as potentially superior and environmentally friendly high-performance construction materials, as they are synthesized by selectively combining waste materials containing alumina and silica compounds which are further activated by a strong alkaline solution. Geopolymers as Sustainable Surface Concrete Repair Materials offers readers insights into the synthesis, properties, benefits and applications of geopolymer-based materials for concrete repair